MORPHOMETRIC AND MERISTIC STUDY OF MANTIS SHRIMP (Harpiosquilla raphidae) IN SEI BEROMBANG WATERS, LABUHANBATU REGENCY, NORTH SUMATERA - Supiana Supiana; Rivo Hasper Dimenta (LP4MK STKIP PGRI Lubuklinggau, 2022)
As basic information on identification process, the morphometric and meristic of mantis shrimp study can be used to initiate of mantis shrimp resource from Indonesia especially from North Sumatera. Mantis shrimp (Harpiosquilla raphidea) have big chance as one of the potential crustacean species as the source nutrition of future but not used optimally. This research was used the quantitative method were determining the sampling point through the purposive random sampling method. This study was conducted from November 2021 to January 2022 in around of Sei Berombang coastal water. The H. raphidea samples was carried out at 3 observation sites using trawl nets. The morphometric result showed that H. raphidea body length size was found range from 8.45 to 30.32 cm. In the meristic analysis of mantis shrimp, there were 5-6 telson spines, 7-8 spines for dactylus, and 15-17 for propodus. These results were described that the body length size of mantis shrimp dominated by small size class. and with this part has confirmed that the mantis found in Berombang estuary waters is H. raphidea.